Cultural Adaptation and Retention : The Narrative Tradition of the African-Caribbean Community of Toronto - Butler, Gary (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1996)
This article discusses strategies for cultural maintenance and adaptation as revealed through an analysis of oral narrative performances among members of Toronto’s African-Caribbean community. Issues related to ethnic and linguistic identification in a contemporary multicultural society are examined in terms of “socialization and secondary enculturation processes” and, more specifically, in the light of traditional folktale material as transmitted in a new setting, to a new generation. The research involved was carried out with funding from the Government of Canada and York University.